Opinion polling behind and across the Iron Curtain: How West and East German pollsters shaped knowledge regimes on communist societies. (October 2016) - Gieseke, Jens
In the context of the Cold War, opinion polling as a method of observation stood for the shift from confrontation and clandestine preparations for a hot or cold civil war towards a competition between systems in the fields of political and cultural attractiveness and economic capabilities. Based on the cases of the West German polling institute Infratest and the East German Institute for Opinion Polling of the Socialist Unity Party, the article highlights the shifts in the external observation and internal self-observation of socialist society with respect to the change in epistemological approaches, research topics, patterns of construction of societal structures and the confluence between political expectations, professional self-understandings and impact on policy-making processes.